PTU-099 Low risk of lamivudine resistance in hbv, hbeag negative patients. time to reconsider?. (22nd June 2015) - Kouroumalis, E; Samonakis, D; Koulentaki, M; Voumvouraki, A
Abstract : Introduction: Lamivudine has been largely replaced for the treatment of chronic HBV infection by new (and more expensive) antivirals with a high viral resistance barrier. It has been reported that lamivudine resistance can be as high as 20% after one year and up to 80% at five years. We therefore assessed a cohort of our patients for the development of Lamivudine resistance over time. Method: 100 chronic HBV hepatitis patients, histologically diagnosed (male 67, female 33), median age 59 years (range 20–75), initially received lamivudine and were followed up for at least 5 years. All were HBeAg negative, HbeAb positive. Genotype D was found in all 23 patients genotyped. All were non-cirrhotic on liver biopsy before treatment (66% Ishak fibrosis stage 2–3, 34% Ishak stage 4–5). Median HBV DNA at the commencement of treatment was 450000 IU/ml. Only 12 patients had a viral load over 1000000 IU/ml. Lamivudine resistance was considered when an increase of 2 logs in the viral load, followed by an aminotransferase increase after an initial response was noted on follow up. Results: All patients responded to lamivudine with normalisation of aminotransferases and subsequent reduction of HBV DNA to less than 100 IU/ml within 6 months from treatment initiation. Lamivudine resistance was 5% at one year, 10% at 2 years, 17% at 4 years and 21% at 5 years Conclusion: The risk for lamivudine resistance development in our chronic HBV hepatitis patients is well below the reported in the literature. Whether this is due to the relative lower levels of viral load or to the lack of cirrhotics in our cohort remains to be further examined. Nonetheless we believe that in view of the low cost, lamivudine use should possibly be reconsidered as a first line treatment In HBV infection for non-cirrhotic patients with a viral DNA below 1000000 IU/ml. Disclosure of interest: None Declared.